Social Content Marketing for Entrepreneurs. - Barry, James M. (Business Expert Press, 2014)
This book will provide a practical overview of how digital content, social media and search engine optimization work together in driving website traffic and sales leads. The goal of the book is to educate readers on the new mindset and social technologies required to drive this traffic in a timely and non-intrusive way. Readers will benefit from a comprehensive but succinct overview of how social networking, search friendly blogging, trustworthy content, contextually-targeted online campaigns and mobile marketing techniques are transforming companies that embrace inbound marketing. Targeted for business professionals and students that are saturated with social technology updates, the book offers a more strategic orientation to these subjects as they relate to sales nurturing and thought leadership. And unlike books that cover social media one platform or technology at a time, this book is organized for readers to master elements of strategy in the order of their implementation. In so doing, it will help order the steps of professionals in the midst of launching new digital marketing initiatives as well as students tasked with completing social media marketing plans.